Illustrating Violence, Mystery and Desolation: Comparing Poe’s Storytelling and Hinds’ Rendering of The Tell-Tale Heart: Exploring the Diversified Narrative Form: An Analysis of Graphic Adaptation of Poe's 'The Tell-Tale Heart' (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Comics might be defined as a hybrid word and image form in which two narrative tracks, one verbal and one visual, register temporality spatially. To appreciate graphic narratives, we need to go beyond the set of rules and re-examine the categories of narratives. Popularly known as “graphic novels”, these illustrations cannot be ignored as an innovative narrative form. A significant difference between children’s comics and graphic novels is that the latter often considered as a more mature counterpart carrying the weight and complexity of a prose narrative or otherwise they are pictorial representations intended to be enjoyed by adults that also include adaptations of classical verbal narratives. In this paper, I stress on the diversification of narrative corpus and appreciate the graphic adaptation of Edgar Allan Poe’s “The Tell-Tale Heart”by Gareth Hinds. Hinds’ graphic narration of “The Tell-Tale Heart” is a part of the 2017 graphic novel adaptation entitled Poe Stories and Poems by Candlewick Press, Massachusetts. Hinds’ illustrations go hand in hand with the gothic tone of the original text, from the symbols of death to the twisted anguished faces. The criminal in the story has executed a horrible crime with rational precision. At the same time he discloses a deep psychological confusion he lacks any normal motivation for the murder. His reasoning tends to convict him of madness. Hinds’ Illustrations portray a slow descent into loss of mind and paranoia. Hinds doesnot dulcorate the blood and butchery in these stories and poems each haunting sequence is full of tension and dread. The graphic novel is a great introduction to Poe’s work. His adaptation depends heavily on the original language of the text while considering the modern reader in mind.